End User Preferences on Hospital Websites in Nigeria - O.Raj, Shakirat; Mahmud, Murni; Md Tap, Abu Osman; Abubakr, Adamu (Little Lion Scientific Islamabad Pakistan, 2013)
This paper presents a Usability study of the Nigerian Hospital websites, through usability testing of some sample hospital websites in Nigeria. The study aims to provide better understanding of the design features and content that offers an easier way of enquiring for some medical advice. Selected participants for the usability testing were given tasks to locate and find specified information in the websites and were evaluated based Nielsen usability heuristics in order to gather the users’ opinion about the websites. The accessibility and availability were also evaluated and the findings indicate huge discrepancies between what people do and what the website are meant for. Each website has its own strengths and weaknesses, but in terms of interactions, our findings reveal that users misunderstand the important of reading instructions provided in websites and prefer direct interaction than by following instruction.